Academic Planning for Faculty Computer Science & Information Technology / Adzni Abdul Rahim - Adzni , Abdul Rahim (2003)
This report will provide a brief description a Smart Academic Planning (SMACAP) for FCSIT is to help the Deputy Dean of Academic to organize the process management in an affectively manner. The scope for this system just for FCSIT because there is different management in education for each faculty; This system provides four important modules such as: